Nations and households in economic growth essays in honor of Moses Abramovitz. - Abramovitz, Moses, 1912-; David, Paul A.; Reder, Melvin W. (Melvin Warren), 1919-2016 (Economic theory and mathematical economics series., 1974)
Nations and Households in Economic Growth.